Induction of Interleukin-10 Producing Dendritic Cells As a Tool to Suppress Allergen-Specific T Helper 2 Responses - Schülke, Stefan (Frontiers in Immunology, 2018)
Dendritic cells (DCs) are gatekeepers of the immune system that control induction and polarization of primary, antigen-speciﬁc immune responses. Depending on their maturation/activation status, the molecules expressed on their surface, and the cytokines produced DCs have been shown to either elicit immune responses through activation of effector T cells or induce tolerance through induction of either T cell anergy, regulatory T cells, or production of regulatory cytokines. Among the cytokines produced by tolerogenic DCs, interleukin 10 (IL-10) is a key regulatory cytokine limiting und ultimately terminating excessive T-cell responses to microbial pathogens in order to prevent chronic inﬂammation and tissue damage. Because of their important role in preventing autoimmune diseases, transplant rejection, allergic reactions, or in controlling chronic inﬂammation DCs have become an interesting tool to modulate antigen-specific immune responses. For the treatment of allergic inflammation, the aim is to down-regulate allergen-specific T helper 2 (Th2)-responses and the associated clinical symptoms (allergen-driven Th2 activation, Th2-driven immunoglobulin E (IgE)-production, IgE-mediated mast cell and basophil activation, allergic inflammation). Here, combining the presentation of allergens by DCs with a pro-tolerogenic, IL-10-producing phenotype is of special interest to modulate allergen-specific immune responses in the treatment of allergic diseases. This review discusses the reported strategies to induce DC-derived IL-10 secretion for the suppression of allergen-specific Th2-responses with a focus on IL-10 treatment, IL-10 transduction, and the usage of both whole bacteria and bacteria-derived components. Interestingly, while IL-10-producing DCs induced either by IL-10-treatment or IL-10 transduction are arrested in an immature/semi-mature state, treatment of DCs with live or killed bacteria as well as isolated bacterial components results in the induction of both anti-inflammatory IL-10- as well as pro-inflammatory, Th1-promoting IL-12 secretion often paralleled by an enhanced expression of co-stimulatory molecules on the stimulated DCs. By the secretion of DC-derived exosomes or CC-chemokine ligand 18 (CCL18), as well as the expression of inhibitory molecules like cytotoxic T lymphocyte–associated antigen 4 (CTLA-4), TNF receptor superfamily member 4 (OX40), Ig-like transcript-22/CD85, or programmed death-1 (PD-1), IL-10-producing DCs have been repeatedly shown to suppress antigen-specific Th2-responses. Therefore, DC-based vaccination approaches hold great potential improve the treatment of allergic diseases.